Optimal vocal therapy for respiratory muscle activation in patients with COPD: effects of loudness, pitch, and vowels - Qiao, Zhengtong; Kou, Ziwei; Zhang, Jiazhen; Lv, Daozheng; Li, Dongpan; Cui, Xuefen; Liu, Kai (Frontiers in Physiology, 2025)
BackgroundVocal therapy, such as singing training, is an increasingly popular pulmonary rehabilitation program that has improved respiratory muscle status in patients with chronic obstructive pulmonary disease (COPD). However, variations in singing treatment protocols have led to inconsistent clinical outcomes.ObjectiveThis study aims to explore the content of vocalization training for patients with COPD by observing differences in respiratory muscle activation across different vocalization tasks.MethodsAll participants underwent measurement of surface electromyography (sEMG) activity from the sternocleidomastoid (SCM), parasternal intercostal muscle (PARA), seventh intercostal muscle (7thIC), and rectus abdominis (RA) during the production of the vowels/a/,/i/, and/u/at varying pitches (comfortable, +6 semitones) and loudness (−10 dB, +10 dB) levels. The Visual Analog Scale (VAS) was used to evaluate the condition of patients concerning vocalization, while the Borg-CR10 breathlessness scale was utilized to gauge the level of dyspnea following the task. Repeated-measure (RM) ANOVA was utilized to analyze the EMG data of respiratory muscles and the Borg scale across different tasks.ResultsForty-one patients completed the experiment. Neural respiratory drive (NRD) in the SCM muscle did not significantly increase at high loudness levels (VAS 7-8) compared with that at low loudness levels (F (2, 120) = 1.548, P = 0.276). However, NRD in the PARA muscle (F (2, 120) = 55.27, P< 0.001), the 7thIC muscle (F (2, 120) = 59.08, P < 0.001), and the RA muscle (F (2, 120) = 39.56, P < 0.001) were significantly higher at high loudness compared with that at low loudness (VAS 2-3). Intercostal and abdominal muscle activation states were negatively correlated with maximal expiratory pressure (r = −0.671, P < 0.001) and inspiratory pressure (r = −0.571, P < 0.001) in the same loudness.ConclusionIn contrast to pitch or vowel, vocal loudness emerges as a critical factor for vocalization training in patients with COPD. Higher pitch and loudness produced more dyspnea than lower pitch and loudness. In addition, maximal expiratory/inspiratory pressure was negatively correlated with respiratory muscle NRD in the same loudness vocalization task.